Inhibitory control in zebrafish, Danio rerio - Lucon‐Xiccato, Tyrone; Bertolucci, Cristiano (Journal of fish biology, 2020)
We assessed whether zebrafish, Danio rerio, display inhibitory control using a simple and rapid behavioural test. Zebrafish were exposed to a prey stimulus placed inside a transparent tube, which initially elicited attack behaviour. However, zebrafish showed a rapid reduction in the number of attacks towards the prey, which indicated the ability to inhibit their foraging behaviour. Zebrafish also exhibited mnemonic retention of foraging inhibition, as indicated by a reduced number of attacks in a subsequent exposure to the unreachable prey. The ability to inhibit the foraging behaviour varied across three genetically separated wild‐type strains and across different individuals within strains, suggesting that zebrafish show heritable within‐species differences in inhibitory control. Our behavioural test might be suitable for screening large zebrafish populations in mutational studies and assessing the effects of pharmacologically active substances on inhibitory control.